1976
DOI: 10.1107/s0567740876006432
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of the enol tautomer of 1,3-diphenyl-1,3-propanedione (dibenzoylmethane) by neutron diffraction

Abstract: The crystal structure of the enol tautomer of 1,3-diphenyl-l,3-propanedione, C15H1202, has been determined from three-dimensional, neutron-diffraction data. The structure was refined by full-matrix, least-squares methods to an R value of 0.090 (0.042 for reflexions with I_>2.3a~) and wR of 0"045 (0.038) using 1660 reflexions. The short, intramolecular O... O contact is 2.463 (4) .~. The enol H atom is asymmetrically placed with respect to the O atoms, the difference in O-H bond lengths being 0.199 (17) ]~. Rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 3 publications
3
36
0
Order By: Relevance
“…T h e earliest studies reported symmetrical O---H-.-O bonding as in structure C (3,4). The consensus of more recent studies is that the bonding is asymmetric as in structures A and B (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 94%
“…T h e earliest studies reported symmetrical O---H-.-O bonding as in structure C (3,4). The consensus of more recent studies is that the bonding is asymmetric as in structures A and B (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 94%
“…1) which prevents the formation of a planar cisoid O1--C3---C2--C5~O2 unit. In support of this, inspection of the structure of the enol tautomer of 1,3-diphenyl-1,3-propanedione (Jones, 1976a) indicates that, although the unique H atom on the central C atom is comfortably accommodated between the phenyl substituents in an essentially planar molecule, it is not possible to accommodate any substituent larger than an H atom at this site without destroying the skeletal planarity. …”
Section: Commentmentioning
confidence: 99%
“…This is most frequently the enol form in which the hydrogen-bonded ring is virtually planar with the two C---O bonds necessarily cis (T~nnesen, Karlsen & Mostad, 1982;TCnnesen, Karlsen, Mostad, Pedersen, Rasmussen & Lawesson, 1983;Etter, Jahn & Urbanczyk-Lipkowska, 1987;Baxter, Blake, Heath & Stephenson, 1990 (Gyepes, Glowiak, Toma & Sold~inov~i, 1984) the ring containing the 1,3-diketone fragment is twisted severely as a result of the ring strain in the [3]ferrocenophane skeleton, so that enolization is again prevented. However, in the acyclic diketone 2-ethyl-1,3-diphenyl-l,3-propanedione, (PhCO)2CHC2H5 (MuUica, Karban & Grossie, 1987), the solid-state structure again indicates a complete lack of enolization associated with a markedly non-planar O==C~C---C==O fragment, although 1,3-diphenyl-1,3-propanedione itself is wholly in the enol form in both crystalline modifications (Jones, 1976a;Etter, Jahn & Urbanczyk-Lipkowska, 1987). In a study of the 1-ferrocenyldiketone [(CsHs)Fe-{(CsH4)COCH2COCH3}], it was found (Bell, Crayston, Glidewell, Mazid & Hursthouse, 1992) that in chloroform solution the enol:keto ratio was ca 17:1, but in the solid state both XSC CP-MAS (cross-polarization magic angle spinning) NMR and X-ray diffraction revealed only the enol form, 1-ferrocenyl-3-hydroxybut-2-en-l-one.…”
mentioning
confidence: 99%
“…1. Final atomic coordinates for the non-hydrogen atoms are listed in Table 1 and interatomic bond lengths and valency angles are in Table 2 (5) 4649 (1) 666 -1822 (8) 4284 (3) 929 -1428 (7) 2047 (2) 675 4590 (5) 4377 (1) 751 11169 (4) 3283 (1) 672 7495 (4) 5171 (1) 654 (Jones, 1976b) and 1,3-diphenyl-1,3-propanedione (III) (Jones, 1976a Jeffrey & Takagi (1978) have suggested that, in order to compare X-ray and neutron diffraction data, the O-H bond lengths of X-ray studies should be normalized to 0.97/k. Contraction of the O(15)-H(15) bond results in parameters that make the asymmetry of (I) appear even more marked.…”
mentioning
confidence: 99%